Occupational accidents with piercing and cutting instruments in hospital nurses - Maria Helena Palucci Marziale; Maria Lúcia Carmo Cruz Robazzi (Fundación para el Desarrollo de la Enfermería, 2004)
Goals: To identify factors associated with occupational accidents caused by piercing and cutting instruments and to identify the consequences of these accidents.Methods: Descriptive field research. Data were obtained through semi-structured interviews with nurses who suffered accidents during one year in four hospitals at São Paulo State - Brazil. Results: factors associated with accidents were: work overload, poor quality material, inadequate disposal materials, professional negligence, clients' aggressiveness, lack of attention and use of unsheathed needles. The accidents caused financial damages to the institutions as well as emotional and physical impairments to workers. Conclusions: There are several factors associated with accidents with piercing and cutting instruments. Therefore, preventive measures must be implemented according to the peculiarities of each work environment. Better care should be taken with the preparation of the professionals as well as with the information on risks from exposure to body/blood fluids they are given. A specific legislation is needed in our country in order to minimize this problem.